A interiorização das ações em saúde no início do século XX em Viçosa (MG – Brasil): The internalization of health actions in the early Twentieth Century: Viçosa, Minas Gerais, Brazil (Revista de História da UEG (REVHIST), 2020)
Abstract: The aim of this article is to analyze the process of health actions’ internalization in the first decades of the twentieth century in Brazil, taking the city of Viçosa / MG as a research stage. The proposal was based on investigating the actions taken by the municipal legislature in relation to health, through legislative documentation, seeking to identify dialogues and points of conflict between the municipal postures and the concerns and guidelines of the central power regarding the sanitation proposals in the period. We also sought to verify the health guidelines in the city of Viçosa, seeking to understand the main measures carried out in the municipality and issues debated by the public authorities.Keywords: Internalization. Public health. Municipal legislation.